Data visualization with JavaScript - Thomas, Stephen A., 1962- (No Starch Press, 2015)
This book shows how to use JavaScript, HTML, and CSS to build the most practical visualizations for your data. Step-by-step examples walk you through creating, integrating, and debugging different types of visualizations and will have you building basic visualizations, like bar, line, and scatter graphs, in no time. Advanced topics include: tree maps, heat maps, network graphs, word clouds, and timelines; map geographic data, sparklines and composite charts; adding interactivity and retrieving data with AJAX; managing data in the browser and building data-driven web applications; Flotr2, Flot, Chronoline.js, D3.js, Underscore.js, and Backbone.js libraries. --